Students' perceptions of mathematics teachers as persons and as subject specialists - Rebollos, Sylvia S.
A questionnaire was administered to selected students from UPHS, Quirino HS, and Ramon Magsaysay HS for an evaluation of their mathematics teachers as persons and as subject specialists on a five-point scale. Findings showed that as persons, mathematics teachers were viewed as democratic, interested in students, friendly, finding enjoyment in teaching, attentive to students' problems and fair. As subject specialists, they were perceived as one who knows the subject matter, expresses himself clearly, systematic, stimulates students' interests, makes the class feel bored and uses visual aids.